2011
DOI: 10.1016/j.jvs.2010.11.127
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of stent-supported subintimal angioplasty in the treatment of long iliac artery occlusions

Abstract: Stent-supported SA in occlusive iliac lesions was safe and showed a high long-term patency rate comparable to that of IA performed in nonocclusive iliac lesions despite longer lesion length. Thus, SA with implantation of stents is an effective technique for the treatment of chronic long iliac artery occlusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 29 publications
3
12
0
Order By: Relevance
“…[5][6][7][8][9][10]12 Treiman et al 5 reported that routine stenting of the entire length of the lesion after SA resulted in primary patency as low as 18% after 3 years, even though the primary patency rates were as high as 85% and 64% at 1 and 2 years. [7][8][9][10]14 In the present study, the 1 and 3 years rates for freedom from restenosis (77% and 59%, respectively) were comparable to previous studies. The primary patencŷT rates of bailout stenting at 1 and 2 years ranged from 55% to 97% and 42% and 94%, respectively.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…[5][6][7][8][9][10]12 Treiman et al 5 reported that routine stenting of the entire length of the lesion after SA resulted in primary patency as low as 18% after 3 years, even though the primary patency rates were as high as 85% and 64% at 1 and 2 years. [7][8][9][10]14 In the present study, the 1 and 3 years rates for freedom from restenosis (77% and 59%, respectively) were comparable to previous studies. The primary patencŷT rates of bailout stenting at 1 and 2 years ranged from 55% to 97% and 42% and 94%, respectively.…”
Section: Discussionsupporting
confidence: 90%
“…Another study by Boufi et al 6 demonstrated that combining SA with a stent-graft along the entire subintimal tract did not improve patency when compared to not receiving a stent. [5][6][7][8][9][10]14 Furthermore, our outcomes were superior compared with the data from Antusevas et al 9 As we reported, we routinely implanted a stent at the proximal stump to keep the entry into the subintimal channel open, and we tried not to cover long lesions with multiple stents because we wanted to avoid stent fractures or difficulties during future bypass surgery. [7][8][9][10]14 In the present study, the 1 and 3 years rates for freedom from restenosis (77% and 59%, respectively) were comparable to previous studies.…”
Section: Discussionmentioning
confidence: 63%
“…For long iliac artery occlusions, a subintimal approach using a 0.035-inch hydrophilic guide wire (Terumo, Tokyo, Japan) supported by a 5F Multipurpose catheter (Torkon NB; Cook) was performed as previously described. 9 All subintimal procedures were performed without the use of re-entry devices. For the treatment of nonocclusive stenotic iliac artery lesions, either an ipsilateral retrograde approach with a 7F introducer sheath (Terumo) or contralateral antegrade approach with a 7F contralateral Balkin (Cook) was used.…”
Section: Angioplasty Proceduresmentioning
confidence: 99%
“…With perpetual improvements in both technology and operator experience, several recent studies have further demonstrated adequate evidence of safety and efficacy with subintimal recanalization and re-entry into the true lumen, with success rates ranging from 71% to 100% [38,39]. Additionally, subintimal revascularization has demonstrated success and safety in chronic total iliac artery occlusions, including long-segment (>5 cm) occlusions [35,40,41]. The TASC authors have noted that when choosing between endovascular and open-surgical or bypass therapies with equivalent short-term and long-term outcomes, endovascular techniques should be used first.…”
Section: Percutaneous Transluminal Angioplasty Versus Stentmentioning
confidence: 99%